Pembelajaran Bahasa Inggris Pada Peserta Didik Kelas 4 Mi Al-Fatah Kedawung Kecamatan Susukan Kabupaten Banjarnegara - Suwarni, Titi; Hidayah, Nahdiyah; Nadziroh, Umi (Hadlonah: Jurnal Pendidikan dan Pengasuhan Anak, 2025)
English is an international language used by major part of the people in the world, so to understand English-speaking, writing, listening and reading- for educated people is a must. Therefore the Indonesian government prepares and declares early in order that English must be taught since Elementary School as a local content. It is hoped that the children will more understand English when they continue their studies at Junior High School, Senior High School and even at University. Teaching English at Elementary school is difficult and unique because students still like playing and do not realize the importance of knowledge. Therefore, it needs competence teachers, suitable materials, method, strategy and media. Because of it, the researcher is interested to discuss it by choosing the title, “Teaching English to the Fourth-Class Students at Madrasah Ibtidaiyah (MI) Al Fatah in the Village of Kedawung in the Subdistrict of Susukan in the County of Banjarnegara.” The researcher wants to know and to describe how the teacher teaches and what strategy, method and media she uses during the process of teaching and learning. The research is qualitative research in form of case study. The approach of the research is phenomenological approach in which the researcher observes the phenomena during the teaching of English and he then describes it. The data is in form of Teaching guideline and the facts happening in the classroom and the source of data is taken from the teacher and from the guide books. The method of research is descriptive-qualitative method meaning the researcher just describes his finding during the process of teaching-learning. The result of the research shows that teacher has taught the students well and successfully. She uses the method of Speech (Ceramah), Q and A /discussion and role play; applies Scientific Approach and Model of Discovery Learning; Uses learning media Guide book Grow with English, instrument of learning LCD Projector etc, and manages the class and time of learning well. Students are enthusiastic to join the lesson, motivated to train and do the homeworks and can understand the lesson optimally.